2022
DOI: 10.1111/pcn.13468
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic progression to schizophrenia: A nationwide cohort study of 11 170 adolescents and young adults with autism spectrum disorder

Abstract: Aims: Previous studies have suggested an increased risk of developing schizophrenia later in life in children with autism spectrum disorder (ASD). This study aims to investigate the diagnosis stability and the potential predictors for progression to schizophrenia in ASD. Methods:We recruited 11 170 adolescents (10-19 years) and young adults (20-29 years) with ASD between 2001 and 2010. They were followed up to the end of 2011 to identify newly diagnosed schizophrenia. The Kaplan-Meier method and Cox regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…For example, Multimorbid3D identified a large genetic intersection between autism and schizophrenia. The connection between autism and schizophrenia has been observed in epidemiological studies (Krieger et al 2021;Hsu et al 2022;Chien et al 2021). Consistent with this, we identified an increased prevalence of schizophrenia in autistic New Zealanders.…”
Section: (Which Was Not Certified By Peer Review)supporting
confidence: 90%
See 1 more Smart Citation
“…For example, Multimorbid3D identified a large genetic intersection between autism and schizophrenia. The connection between autism and schizophrenia has been observed in epidemiological studies (Krieger et al 2021;Hsu et al 2022;Chien et al 2021). Consistent with this, we identified an increased prevalence of schizophrenia in autistic New Zealanders.…”
Section: (Which Was Not Certified By Peer Review)supporting
confidence: 90%
“…Our analysis identified genetic variants that are associated with traits that are known to co-occur with autism (e.g. schizophrenia (Krieger et al 2021;Hsu et al 2022;Chien et al 2021) and BMI (Croen et al 2015)). We contend that the results of this study provide a starting point for the individualized stratification of the biological mechanisms linking autism and its co-occurring traits.…”
Section: Discussionmentioning
confidence: 99%
“…Given overlaps between ASD and SSD (Jutla et al, 2022 ), this is a crucial issue. For example, a recent nationwide cohort study of 11 170 adolescents and adults with ASD found a progression rate to schizophrenia of 10.26% (Hsu et al, 2022 ; Lugo Marín et al, 2018 ). To tackle this issue, future studies must conduct comprehensive differential diagnostic assessment of their sample, including their ASD groups.…”
Section: Discussionmentioning
confidence: 99%
“…We performed a de novo network analysis of cortical GRNs that identified four genes that are causal for autism within the 17q21.31 loci in fetal tissue ( LINC02210 , LRRC37A4P, RP11-259G18.1, and RP11-798G7.6 ), of which, LINC02210 was also identified as being causally related to autism in adult tissue. Our analysis identified genetic variants that are associated with traits that are known to co-occur with autism (e.g., schizophrenia [ Chien et al, 2021 ; Krieger et al, 2021 ; Hsu et al, 2022 ) and BMI ( Croen et al, 2015 ]). We contend that the results of this study provide a starting point for the individualized stratification of the biological mechanisms linking autism and its co-occurring traits.…”
Section: Discussionmentioning
confidence: 99%